Privacy and Data Protection in the European Parliament: An Interview with Sophie in ‘t Veld - Taylor, Mistale (Utrecht Journal of International and European Law, 2015)
Sophie in ‘t Veld, of the Dutch social liberal party Democrats 66, is a Member of the European Parliament (hereafter: MEP). She is Vice President of the Alliance of Liberals and Democrats for Europe. In ‘t Veld has a specific interest in issues of privacy and data protection. As such, she is a member of, inter alia, the European Parliament’s LIBE Committee on Civil Liberties, Justice and Home Affairs, whose tasks include reviewing the EU’s proposed data protection reform package. She is also Chair of the European Parliament’s Privacy Platform. In the interview below, conducted on 7th November, 2014, In ‘t Veld elaborates on how the EU protects, or aims to protect, its citizens’ rights to privacy and data protection.